THE WAR IN UKRAINE - A LONG TERM CONFLICT - Dincă, Marian; Dincă, Alexandru-Marian (International Journal of Legal and Social Order, 2024)
European security has been severely shaken by the Russian Federation's surprise invasion of Ukraine in February 2022. The causes and determinants, as well as the implications of this conflict, require a broader, more comprehensive approach, starting from the events of 2014. The conflict in Ukraine is and will remain a hot topic of utmost interest due to its political-military and economic-social implications, at a global level. The outlook for the conflict in Ukraine remains uncertain and dependent on a whole range of factors and circumstances.